Floristic diversity and composition of heath forest in Kuala Tambangan Village, Tanah Laut District, Indonesia - MOCHAMAD ARIEF SOENDJOTO; MAULANA KHALID RIEFANI; SHERLI DIANA (Society for Indonesian Biodiversity, 2023)
Abstract. Soendjoto MA, Riefani MK, Diana S. 2023. Floristic diversity and composition of heath forest in Kuala Tambangan Village, Tanah Laut District, Indonesia. Biodiversitas 24: 5418-5427. Heath forest (kerangas) is a unique ecosystem characterized with sandy soil with poor nutrients. This harsh condition makes heath forest has unique vegetation diversity as well as vulnerable to disturbances. In South Kalimantan, there is a heath forest located in Kuala Tambangan, Tanah Laut District which has never been explored. The research aims to analyze the diversity and composition of vegetation community in heath forest in Kuala Tambangan and identify factors that have the potential to damage the forest. Data was collected using the transect method placed at three sites in the heath forest. Along each transect, 10 observation plots with size 20 m × 20 m were established to record woody plants at the tree level. Within this plot, nested plots with size of 10 m × 10 m was created to record plants at pole level, 5 m × 5 m for saplings and herbaceous plants and 2 m × 2 m for seedlings, ferns and grasses. In total, there were 85 plant species across all observation plots with 79 species were found in the heath soils. Some typical heath forest species were found such as Melaleuca sp., Baeckea frutescens L. and Cratoxylum formosum (Jack) Benth. & Hook.fil. ex Dyer. Important Value Index (IVI) as well as Shannon-Wiener diversity index (H') varied, both by plant group and by study site. For example, the highest IVI of the tree group belonged to Acacia crassicarpa A.Cunn. ex Benth. and Acacia mangium Willd., and for pole level was Melaleuca sp. The lowest diversity occurred at Site B, while the highest was at Site C. The results on vegetation diversity, structure and composition suggest that this forest is in degraded condition. Fires and land conversion are factors that threaten the existence of heath forest in Kuala Tambangan. Our findings recommend the needs of efforts to protect and restore this unique ecosystem.